Towards realizing the Maqasid Al-Shariah: a critique of Islamic banking and finance practices - Nor Azmi, Hamzah Syahir; Kayadibi, Saim (IIUM Press, 2011)
There has been phenomenal growth in the Islamic banking and finance (IBF) industry since its nascent introduction just slightly over 1'0111' years ago. In Iran, Pakistan. and Sudan, only Islamic banking is allowed. In other countries, such as Bangladesh, Egypt, Indonesia, Jordan and Malaysia, Islamic banking coexists with conventional banking. Islamic banking, moreover, is not limited to Islamic countries. In August 2004, the Islamic Bank of Britain became the first bank licensed by a non-Muslim country to engage in Islamic banking. The HSBC, University Bank in Ann Arbor and Devon Bank in Chicago offer Islamic banking products in the United States. Recent industry estimates showe that Islamic banking, vvhich managed around U5$250 billion worth of assets worldwide as of2004 (Chong & Liu, 2007). Consequently, Islamic banking and finance has emerged as one of the fastest gro\ving industries, and is expected to grovv' at the rate of 15% per annum. It has spread to all comers of the globe and received wide acceptance by both Muslim and non-Muslim alike (Iqbal & Molyneux, 2005).